AB0581 Comparable Survival for Filipino Pediatric Lupus Nephritis Even Without Kidney Biopsy. (9th June 2015) - Taleon, K.J.B.; Tee, C.
Abstract : Background: Kidney biopsy is an important diagnostic tool in planning the treatment for lupus nephritis. [1] However, there are circumstances in which biopsy could not be done and treatment has to be rendered immediately. In lieu of this, the Sections of Rheumatology and Nephrology developed a treatment protocol based on clinical data and laboratory findings for pediatric lupus nephritis. [2] Objectives: To describe the clinical profile and outcomes of lupus nephritis pediatric patients in a tertiary care hospital and to compare the clinical outcomes of pediatric patients with SLE nephritis who underwent immunosuppressive therapy guided by kidney biopsy to those who did not but were guided by treatment protocol developed by the sections of Rheumatology and Nephrology of the tertiary hospital. Methods: This is a retrospective study, which included all patients less than 19 years old diagnosed with lupus nephritis. Patients were categorized depending whether or not treatment plan is guided by the results of a kidney biopsy. The outcome of the patient, effect of treatment and progression to end stage renal disease (ESRD) were measured. Results: Thirty-one cases of lupus nephritis with mean age of diagnosis at 14.4±2.48 years were included. There were 27 females (87%). Common presentations of renal involvement included edema (74.2%), hematuria (61%), and hypertension (51.6%). Eleven patients had kidney biopsy; the most common classification is class III lupus nephritis (45.4%). The average interval of 7.4±4.08 months from start of induction to performance of biopsy was noted. Majority of the patients were in remission until 18 months study period and five patients died in the said duration. The causes of death identified were septic shock (4) and multiple organ dysfunction (1). The probability of survival is 90% at 6 months and 12 months, and 80% at 18 months. Conclusions: In our clinical series of 31 patients, lupus nephritis affects females more than males. All patients had immunotherapy before the kidney biopsy was done. Seventy two percent of the patients were in remission by the end of 18 months. Causes of 5mortalities were severe sepsis and multiple organ dysfunction syndrome. Probability survival for patients is noted to be 90% for the first 6-12 months and 80% at 18 months. Clinical findings of pediatric lupus nephritis seem to correlate well with histopathology and the lack thereof should not delay the treatment. References: Bertsias et al: Joint European League against rheumatism and European Renal Association-European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations for the management of adult and pediatric lupus nephritis. Annals of Rheumatic Diseases 2012: 71: 1771-1782. Gulay and Dans: Clinical presentations and outcomes of Filipino juvenile systemic lupus erythematosus. Pediatric rheumatology 2011 9:7. Disclosure of Interest: None declared